Bovine Ephemeral Fever pada ternak sapi potong di Kabupaten Gunungkidul, Yogyakarta (Laporan Kasus) - Alfarisa Nururrozi; Mulya Fitranda; Soedarmanto Indarjulianto; Yanuartono Yanuartono (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
Bovine Ephemeral Fever (BEF) or three days sickness is one of the most common disease in cattle. The disease is caused by rhabdoviridae virus transmitted  through mosquito as a vectors. This paper aims to determine the incidence of BEF cases in Gunungkidul district, Yogyakarta. Diagnoses BEF based on information collected through the anamnesis from owner and the results of clinical examination. 134 (48%) from 277 cows were examined in the   Gunungkidul district period October-November 2016 diagnosed BEF. Clinical signs were found consist of anorexia 111 cases (34%), hyperthermia 99 cases (31%), lameness 42 cases (13%), cow downer 31 cases (10%), nasal discharge 35 cases (11%) and hypersalivation  6 cases (2%). Bovine Ephemeral Fever mayority reported on the second day of the disease progression by 67 cases (42%). The most common therapy  used combinations of antipyretics, antibiotics and vitamins were 45 cases (33%). Based on the information from the farmers, the treatment has given good results and absence of  the absence of post-treatment recurrence